Increased mitochondrial proton leak and glycolysis in peripheral blood mononuclear cells in type-1-diabetes - Joana Mendes Lopes de Melo; Jens Christian Laursen; Niels Søndergaard-Heinrich; Ida Kirstine Bull Rasmussen; Christian Stevns Hansen; Marie Frimodt-Møller; Peter Rossing; Joachim Størling (Heliyon, 2022)
Changes in cellular bioenergetics such as mitochondrial respiration and glycolysis may play a role in the pathogenesis of various diseases including type 1 diabetes (T1D). We used Seahorse extracellular flux technology to analyse the efficiency of glycolysis and mitochondrial oxidative phosphorylation in peripheral blood mononuclear cells (PBMCs) obtained from fresh blood samples from fifteen long-term T1D individuals with albuminuria (five females) with an average (±SD) age of 58 (±14) years and 15 age and sex-matched healthy non-diabetic controls. In T1D PBMCs, mitochondrial proton leak was higher (T1D: 21,3 ± 1,46 pmol/min; controls: 17,3 ± 1,24 pmol/min; p = 0,049) and glucose (5 mM) suppressed mitochondrial proton leak more than in healthy controls. Further, PBMCs from T1D individuals had higher glycolysis compared with healthy controls (T1D: 9,68 ± 0,94 mpH/min; controls: 7,07 ± 0,64 mpH/min; p = 0,032). Correlation analysis of circulating inflammatory factors identified Leukaemia Inhibitor factor 1 (LIF) being negatively correlated with PBMC glycolysis. Our results suggest that mitochondrial and glycolytic pathways of PBMCs from long-term T1D individuals with albuminuria might be dysfunctional, possibly due to increased cellular metabolic load and/or oxidative stress in which inflammatory factors could play a role.